Características do gestor, composição das carteiras e desempenho dos fundos multimercados brasileiros - Maestri, Cláudia Olímpia Neves Mamede (2016)
This work aims to contribute to the literature on investment funds in emerging markets to address the portfolio composition and performance of Brazilian hedge funds under the manager's perspective. This is because in emerging countries an efficient allocation of assets in the portfolios of the funds is subject to different risk characteristics of the active participants of these portfolios, in addition to the composition of the portfolios be a possible explanation for the differences in performance of the funds. Moreover, from the perspective of the manager, the choice of the assets that make up their portfolios and the performance of the funds it manages, may be subject to the influence of special features such as: experience, amount of funds under management, manager location and managers who have better performance than your peers. So the problem that prompted this research was: which variables related to the manager affect the portfolio composition and performance of hedge funds? Therefore, the Brazilian hedge funds registered with the CVM were analyzed, considering free survival bias samples for the period from September 2009 to January 2016. The first sample included 6,659 funds with 327,270 monthly observations and the second involved 5,309 funds, with an equal number of observations as contemplated indicators for the period. Hypothesis tests were conducted by econometric techniques in Stata® software. The results showed that the composition of the portfolio is influenced by characteristics of managers, as experience, amount of funds under management, manager and location managers who have better performance than their peers. These features of the manager, the experience and the amount of funds under management are also important to explain the performance achieved by hedge funds, beyond this be explained by the allocation of fixed and variable income assets. It should be noted that, when considering the confidence interval of the coefficients of these variables, the composition of the portfolios (fixed and variable income) is presented as the main factor that helps to explain a potential change of the performance of Brazilian hedge funds.